A Comparative Review of Classical and Modified Periodogram Used As the Technique of Estimating Spectrum in Spectral Analysis: Comparing classical and modified periodograms for spectral analysis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Periodogram is a non-parametric approach for estimating power spectrum in spectral analysis when sinusoids are fitted in discrete time series data. The performance of the Periodogram has always been measured based on spectral leakage, resolution, bias and variance. Thus from time to time, for getting better results from this technique, changes are made by various research workers and hence modified versions of Periodogram are introduced. In this paper reviews on original work of Schuster and Fourier periodograms are compared with the modified periodograms.